2015
DOI: 10.1007/s11999-015-4258-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Rotator Cuff Repair Improve Psychologic Status and Quality of Life in Patients With Rotator Cuff Tear?

Abstract: Background Recently, psychological status, patient-centered outcomes, and health-related quality of life (HRQoL) in patients with scheduled or who underwent orthopaedic surgeries have been emphasized. The relationship between preoperative psychological status and postoperative clinical outcome in patients with rotator cuff repair has not yet been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 24 publications
5
113
0
11
Order By: Relevance
“…Future studies could focus on the prevention of psychological symptoms after shoulder surgery, for example by cognitive treatment, and observe the effect on clinical outcome. Two recent studies, with small study populations, evaluated preoperative psychological distress and functional outcome after rotator cuff surgery [18,19]. Their results are in line with the results found in this study that preoperative symptoms of psychological disorders were not negatively associated with functional outcome after shoulder surgery.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Future studies could focus on the prevention of psychological symptoms after shoulder surgery, for example by cognitive treatment, and observe the effect on clinical outcome. Two recent studies, with small study populations, evaluated preoperative psychological distress and functional outcome after rotator cuff surgery [18,19]. Their results are in line with the results found in this study that preoperative symptoms of psychological disorders were not negatively associated with functional outcome after shoulder surgery.…”
Section: Discussionsupporting
confidence: 87%
“…In orthopaedic literature, preoperative psychological distress such as depression and anxiety has been reported to be associated with worse clinical outcomes after surgery of the hip, knee and lumbar spine [16,17]. In two recent studies, preoperative psychological distress was not associated with clinical outcome after rotator cuff surgery [18,19]. If, however, preoperative psychological status appears to have an impact on the outcome after shoulder surgery, then the identification and treatment of psychological disorders should be an essential part of the preoperative assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Through the implementation of arthroscopic rotator cuff repair, it was found that the joint function, the sleep quality, the anxiety situation and the quality of life of patients has been signi cantly improved during the 2-year follow-up. But the impact on depression was not signi cant, which was consistent with the study of Cho C et al [19]. and Kennedy P et al [20].…”
Section: Discussionsupporting
confidence: 90%
“…However, to our knowledge, no studies have sought to correlate cervical sagittal realignment for patients with kyphotic cervical deformities from tuberculosis with improvements to patient-reported outcomes, which questionnaires generally are multidimensional, and assess a combination of aspects of impairments and/or disability. They reflect a patient's health status, and are means of gathering patients' views on recovery [3,12]. Lee et al [10] reported that patient-reported outcomes are associated with cervical sagittal alignment, however, not specifically in this population of patients.…”
Section: Introductionmentioning
confidence: 99%